Vitality characteristics of Аllium species coenopopulations іn the Мykolayiv Region (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Populationsof seven speciesof AlliumL. were studied in the Mykolayiv Region with evaluating. vitality of individuals and quality and vitality type of coenopopulations. It is revealed, that negative changes in vitality structure of populationare caused by strengthening of human activity impact.
Keywords: Mykolaiv region, nature-reserve territories, Allium L. species, average plant weight , average plant height, total number of flowers, vitality structure, vital type of population.